As crianças e o conforto térmico: sensações e preferências térmicas em escolas de ensino fundamental no clima quente e úmido - Souza, Jullyanne Ferreira de (2020)
The lack of attention to the minimum requirements about thermal comfort in schools, can compromise the quality of work and the health of its users, whether they are teachers, workers or students, in addition to impairing the students' learning process. Due to the few studies about Thermal Comfort with children done in Northeast Brazil, the present research begins its investigation in an analysis of perception and sensation of thermal comfort in schools in the Rede Municipal de Ensino in the city of João Pessoa - PB. The investigation intended to identify the thermal sensations and preferences of children, from the last years of elementary school, with the age range of 8 to 11 years old. The research methodology consisted of measuring environmental variables (identifying) and, simultaneously, applying questionnaires adapted to children. The experimental stage of the work occurred during the months of August, September, November and December of the year 2018. A total of 712 questionnaires were administered to children (410 in winter and 302 in summer). These questionnaires presented four questions regarding sensation and preference, in naturally ventilated rooms and air-conditioned rooms, while the environmental variables were measured simultaneously. The results show that in summer and winter most children felt some discomfort due to heat and preferred it to be cooler. Also in both periods, in schools with natural ventilation more children reported heat than in artificially conditioned schools, this difference was more pronounced in summer than in winter. However, the thermal performance was not satisfactory in any of the two types of environments, since, the best result found is 35,06% of the votes in the sense of neutrality, in artificially conditioned classrooms in winter, and considering votes -1 and 1 also as comfort, 71.84%. Regarding votes of preference for air-conditioned environments, most children in all rooms and all periods, reported preferring the use of air conditioning, what shows an association on their part between comfort and air conditioning. In statistical analysis, it was found that, on average, male students have more heat sensation than female students, however, no differences were found in relation to preference. Regarding the body mass index, it was possible to state that, in all classrooms, the higher the body mass index, the higher the number of students with a preference for cold environments. The PMV and Adaptive prediction models underestimated the feelings reported by the students. It was examined that children who were in naturally ventilated environments, had a greater tolerance for higher temperatures than children subjected to acclimatized environments. In the winter, the votes of neutrality, of children from naturally ventilated schools, occurred in the air temperature range between 27 °C and 29,50 ° C, while in artificially conditioned schools in the range between 26.00 ° C and 27,50°C. In the summer, the votes of neutrality, of the children from the naturally ventilated schools, occurred, in the air temperature range between 27,00 °C and 28,00°C, while in the artificially conditioned schools in the range between 26,00 °C and 27,50°C, as in winter.